Implementasi Program Keselamatan dan Kesehatan Kerja pada PT. Jtekt Indonesia Jawa Barat dalam Meningkatkan Produktivitas Pekerja - Bachri, M. Ravi Faizal; Mukhlisin, Mukhlisin; Fauzi, Rian; Rusliyandi, Rusliyandi (DPPM UNIVERSITAS PELITA BANGSA, 2025)
This research aims to examine the implementation of the occupational safety and health (K3) program at PT Jtekt Indonesia, as well as identifying the obstacles faced in implementing the program, This research focuses on the efforts made to overcome various obstacles, used qualitative descriptive, data collection uses observation, interviews and documentation. This research involved several key informants who contributed valuable insights. namely the head of the Safety, Health and Environment (SHE) member who is an K3 expert, as well as three SHE members and employees from the product warehouse section as additional informants. This study employs an interactive model analysis approach. The findings indicate that the implementation of K3 program at PT Jtekt Indonesia has had a positive impact on work productivity. Through interviews conducted, there was an productivity 15.41% compared to before the WISE program was implemented in the company. Programs implemented include: (1) K3 development through proactive communication methods, training and motivation; (2) Supervision using behavioral safety audit methods and work accident reporting; (3) Provision of K3 facilities and equipment, including toilets, employee changing rooms, locker rooms, first aid boxes, canteens, cooperatives, rest areas, polyclinics, and personal protective equipment (PPE).However, there are several obstacles in implementing K3, such as a lack of employee awareness in using PPE and low employee understanding of the importance of K3. To overcome these obstacles, the company made various efforts, including providing safety orientation, training and retraining, counseling, as well as providing written and verbal warnings balanced with strict supervision from management.